Isolated thoracoschisis - Basem Saied Abdelkader; Mahmoud Ahmed Ahmed Abdelbary; Amer Nihal Ahmed (Elsevier, 2020)
Thoracoschisis is a rare congenital anomaly that affecting the thoracic wall. The present case is the seventh case of isolated thoracoschisis in the literature. A male infant was born at 37 weeks via spontaneous vaginal delivery and was found to have a left sided chest wall defect measuring 2 × 2 cm with eviscerated abdominal contents including Riedel's lobe of the liver, stomach, and transverse colon. Reduction of herniated viscera with closure of the defect few hours after delivery.